SCIENTIFIC AND METHODOLOGICAL FOUNDATIONS OF IMPROVING THE SOFTWARE OF THE DISCIPLINE "DATA STRUCTURE AND ALGORITHMS" WITH THE USE OF DIGITAL TECHNOLOGIES (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article explores the scientific and methodological foundations for improving the software of the subject “Data Structures and Algorithms” through the use of digital technologies. The study emphasizes the critical role of this subject in shaping students’ algorithmic thinking, problem-solving skills, and practical programming abilities. Traditional teaching approaches are analyzed and compared with modern digital methods, highlighting their limitations in providing interactive, visual, and practice-oriented learning experiences. Based on this analysis, a methodology for enhancing the subject’s software is proposed, incorporating interactive visualization tools, automated assessment systems, and digital learning platforms. The research further includes experimental trials that demonstrate the positive impact of digital technologies on learning outcomes, particularly in improving knowledge acquisition, analytical skills, and student motivation. The results confirm that digital modernization of teaching software ensures higher efficiency, deeper understanding, and broader opportunities for learners.